Behavioral Problem among School-Age Children in a Community - Shah Haluwai, Sarita; Bhattarai, Jamuna (Journal of Biratnagar Nursing Campus, 2025)
Introduction: Bhavioral problems are the reactions and clinical manifestations resulting from emotional disturbances or environmental maladjustments. The objective of this study was to find out the behavioral problems of school-age children in a community.Methods: A descriptive cross-sectional study was conducted among school-age children in Ward No. 2 of Hetauda, Makawanpur. A non-probability purposive sampling technique was used to recruit 112 samples. Face-to-face interviews were conducted using a standard tool (Rutter's Children's Behavioral Questionnaire) for data collection. The obtained data were entered using SPSS version 16 and analyzed using descriptive statistics to find the mean, standard deviation, and frequency percentage. Inferential statistics (Chi-square) was used to measure the association of variables.Results:  The results showed that, out of 112 respondents, most of the children (89.3%) had normal behavior, and only 10.7% of children had moderate behavioral problems. Behavioral problems were significantly associated with the education status of mothers (p-value < 0.033).Conclusion: The study concludes that the majority of children exhibited normal behavior, while few showed moderate behavioral problems. These behavioral problems were significantly associated with the education level of the mothers. There is a need to raise awareness about the behavioral problems of school-age children to improve the of behavioral issues among children. Screening is necessary to detect behavioral problems in school-age children.